2010
DOI: 10.1111/j.1600-0722.2010.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prion gene and presence of prion protein during development of mouse molar tooth germ

Abstract: In order to gain insight into possible cellular functions of the prion protein (PrP) during normal development, the expression of Prnp (encoding the PrP) and the distribution of the PrP were studied in murine tooth germs. Expression of Prnp in the mouse first molar tooth germ was highly dynamic, increasing several-fold during the secretory phase of odontogenesis, exhibiting a time-course of expression similar to that of genes coding for other extracellular proteins [e.g. enamel matrix proteins (Amelx, Ambn, En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
5
1
Order By: Relevance
“…The in situ results for Amelx , Amb n, and Enam mRNA showed similarities with immunohistochemical localization of Serpinb5, Clusterin, and Prnp (French et al, 1993; Davaadorj et al, 2010; Khan et al, 2010). Expression of enamel proteins in bone cells has previously been reported (Spahr et al, 2006; Tamburstuen et al, 2010; Tamburstuen et al, 2011) and is supported by the presented in situ data.…”
Section: Discussionsupporting
confidence: 52%
“…The in situ results for Amelx , Amb n, and Enam mRNA showed similarities with immunohistochemical localization of Serpinb5, Clusterin, and Prnp (French et al, 1993; Davaadorj et al, 2010; Khan et al, 2010). Expression of enamel proteins in bone cells has previously been reported (Spahr et al, 2006; Tamburstuen et al, 2010; Tamburstuen et al, 2011) and is supported by the presented in situ data.…”
Section: Discussionsupporting
confidence: 52%
“…Our observations reported in this study are consistent with the previous findings that PrP C is localized in human and mouse odontoblasts (Manson et al, 1992, Schneider et al, 2007, as well as secretory ameloblasts in the developing tooth organ (Khan et al, 2010). However, our immunolocalization analysis showed PrP C highly localized in the apical border as well as lateral cell membranes, particularly in secretory odontoblasts and ameloblasts.…”
Section: Discussionsupporting
confidence: 81%
“…Using microarray expression data from molar tooth germs from mice treated with anti‐miR‐214, a profile search using the results for Clu and Tgfb1 as search criteria led to the isolation of a cluster of 35 genes, which also included Ambn , Amelx , and Enam . Eight of the genes [ Ambn ; Amelx ; Clu ; Enam ; laminin, beta 3 ( Lamb3 ); papilin, proteoglycan‐like sulfated glycoprotein ( Papln ); Prnp ; and solute carrier family 25 (mitochondrial carrier, glutamate), member 22 ( Slc25a22 )] had also been observed in a previous study .…”
Section: Resultsmentioning
confidence: 81%
“…In a previous study, expression of the prion protein ( Prnp ) gene in murine molar tooth germs was shown to increase at postnatal developmental stages. The time‐course of expression of Prnp was similar to that of genes encoding enamel proteins [ameloblastin ( Ambn ), amelogenin X chromosome ( Amelx ), and enamelin ( Enam )] and also to that of clusterin ( Clu ) . In contrast, genes associated with regulation of organ growth [e.g.…”
mentioning
confidence: 92%